1981
DOI: 10.3109/01485018108987348
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Studies in Reproductive Immunology, 3. Restoration of Mitogenic Activity of Lymphocytes Inhibited by Seminal Plasma in Man

Abstract: Human seminal plasma, (HuSePl) is inhibitory to mitogen (PHA-M, Con-A, and PWM) lymphocyte activation. The inhibition does not require the continuous presence of HuSePl. Lymphocyte cultures remain inhibited after 24-hr contact with HuSePl and subsequent washings. Addition of fresh autochthonous lymphocytes or T cells but not B cells can restore the mitogenic activity of HuSePl-inhibited lymphocyte cultures. These observations suggest that T-lymphocyte in the male genital tract are surveilled by HuSePl and lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The free fraction of the inhibitory factor will consequently vary in concentration and thus activity. Normozoospermic semen will tend to cause less suppression of the lymphocytes than qeminal plasma from an azoospermic male [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The free fraction of the inhibitory factor will consequently vary in concentration and thus activity. Normozoospermic semen will tend to cause less suppression of the lymphocytes than qeminal plasma from an azoospermic male [7].…”
Section: Discussionmentioning
confidence: 99%
“…although there was greater inhibition with seminal plasma fractions than with whole seminal plasma. It may be necessary to isolate the inhibitory component of human seminal plasma to demonstrate individual differences in the immunosuppressive activity of seminal plasma [ 7 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Fractionation studies have shown that large proteins, some of which are of vesicular origin, are involved (Lord, Sensabaugh & Stites, 1977;Marcus & Hess, 1981;Stites & Erickson, 1975;.…”
Section: Action Of Vesicular Secretions On the Female Genital Apparatusmentioning
confidence: 99%